CRIMINAL PSYCHOLOGY AND IMPACT OF RECENT GLOBAL PANDEMIC: ANALYSIS OF CRIMINAL MIND WITH A SUDDEN SURGE IN CRIME RATE - Hemlata Bhagtani, Seema Roj, Dr. Kiran Raj (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The year 2019 was marked with the 2019-CoVID pandemic attack, a widespread contagious effect of newvirus of coronavirusfamily. This pandemic attack was widely followed by nationwide lockdown which possessed negative impact on the economy of India. Thus, resulting in depreciation in the living standards of the people corona created a crime-reflux in the country. The extended contagious nature of the corona virus came as boon for the criminals bugging India as government released thousands of prisoners from jail while hearings in most of the cases were adjourned. This action boosted their and their prospective like ones confidence. Though harsh physical crime reduced during the lockdown period yet an illicit increase was noticed in cyber crime, terrorism, illegal-markets and-smuggling, robberies and burglaries. Criminals started diversifying in other areas and branches of criminal activities. Exploiting the public information on crime in India,along with relying on routine-activity and pattern-theories of crime, this work-investigates whether and how new-coronavirus containment policies affected criminal psychology.The study will be useful to understand the impact of COVID 19 situations and policies made to take shelter againstit on the criminal psychology with specific reference to India. The study also attempt to suggest practical solutions to mitigate the development and consequences of criminal psychology.